(untitled) - Fiske-Rusciano, Roberta (New York, 2005)
This book is divided into three main division: "Identity", "Power" and "Change". It is guide for students in the thoughtful exploration of the issues that sorround personal and insitutionalized bigotry.
Keywords: Pluralism (Social sciences),Gays,Women,Đa nguyên (Khoa học xã hội),Đồng tính nam,Phụ nữ; Social conditions,Social conditions,Mỹ,Điều kiện xã hội,Điều kiện xã hội; Mỹ,Mỹ; United States,United States,United States